Inclusive education’s promises and trajectories: Critical notes about future research on a venerable idea - Artiles, Alfredo J.; Kozleski, Elizabeth B. (Education Policy Analysis Archives, 2016)
The purpose of this article is to offer critical notes on inclusive education research in the U.S. We discuss issues germane to conceptual clarity and the ways in which inclusive education interacts with reforms that share equity goals, noting disruptions and unintended consequences that arise at the nexus of these reforms. In addition, we identify enduring challenges and paradoxes in this research literature. These include sampling issues, an emphasis on where students are placed as a proxy for inclusive education vis-à-vis inclusive education as the transformation of educational systems, the ways in which outcome measures have been examined in this research, and the need for and challenges of building strategic alliances that could advance an inclusive education agenda. We conclude with reflections and suggestions for a future research program that include sharpening inclusion’s identity, attending to the fluid nature of ability differences and students’ multiple identities, broadening the unit of analysis to systems of activities, and documenting processes and outcomes.